An analysis of counselor case studies in the public secondary schools of Manila - Lolarga, Erlinda (Garcia) 1929- (1966)
The case studies that represent the first attempts at the case study technique for use in consultation sessions with the Philippine Mental Health Association Guidance team are analyzed in order to determine the problems covered by the case studies as identified by guidance counselors, the data that have been utilized in these case studies, and the characteristics of the case studies.
Thesis (M.Ed.)--University of the Philippines
Keywords: Counselling -- Case studies